Complete Response to Immunotherapy Combined With Chemotherapy in a Patient With Gynecological Mixed Cancer Mainly Composed of Small Cell Neuroendocrine Carcinoma With High Tumor Mutational Burden: A Case Report - Su, Xingyun; Zhou, Xinhui; Xiao, Cheng; Peng, Wei; Wang, Qiangfeng; Zheng, Yulong (Frontiers in Oncology, 2022)
Small cell neuroendocrine carcinoma (SCNEC) is rare in gynecologic tract, which has high invasive and metastatic ability. Due to the aggressive behavior and lack of treatment, patients have extremely poor prognosis. Here we reported a 66-year-old female diagnosed as SCNEC in gynecologic tract, mixed with endometrioid adenocarcinoma, squamous cell and adenosquamous carcinoma. High tumor mutation burden of 13.14 Muts/Mb was detected by next generation sequencing. The patient underwent palliative operation of total hysterectomy with bilateral adnexectomy, but suffered from disease progression in a short time after operation. Chemotherapy (Taxol + Carboplatin) combined with immunotherapy (Toripalimab) were conducted every three weeks, achieving a good partial remission after 2 cycles of treatment. After 5 cycles, the patient consolidated with monotherapy of Toripalimab for about half a year and experienced a complete remission. Until June 2021, the patient has achieved 21-month of progression free survival and maintains continued complete remission. This case is presented due to the rare combination of pathological types and durable response to immunotherapy, suggesting the potential value of immunotherapy in SCNEC of gynecologic tract.